Raising Healthy Children: Milk and Egg Allergies - Jonathan Holzinger; Karla Shelnutt; Gail Kauwell (EDIS)
Milk and eggs are familiar, nutritious foods that most children enjoy, but these foods can cause problems for children with milk and egg allergies. If your child is allergic to milk or eggs, you need to consider steps you and your child can take to avoid these foods, and you need to make sure your child gets enough of the proper nutrients, especially if certain foods are removed from his or her diet. This 5-page fact sheet will help you learn more about milk and egg allergies and how to make sure your allergic child stays safe. Written by Jonathan Holzinger, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, February 2013.